2019
DOI: 10.3832/ifor3082-012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stand density on longitudinal variation of wood and bark growth in fast-growing Eucalyptus plantations

Abstract: The influence of tree spacing on the wood/bark ratio is unknown in young fastgrowing Eucalyptus trees. The objective of this study was to evaluate the effect of plant spacing on the wood and bark production along the Eucalyptus stem. Four genetic materials were planted in four spacings: 3×1 m, 3×2 m, 3×3 m and 3×4 m. Three 5-year-old trees from each clone and in each plant spacing were harvested. Cross-sectional discs (thickness: 30 mm) were cut from each tree along the stem (0%, 25%, 50%, 75% and 100% of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…For dendrometric parameters, the average DBH, height and volume are in accordance with what was expected for Eucalyptus urophylla at the age of 8 years, as can be seen in the study of Trugilho et al (2010). Regarding the bark percentage, the results are in harmony with the studies obtained by Ramalho et al (2019) who found values for Eucalyptus urograndis between 10 and 18%. In a general way, according to Neiva et al (2018) bark percentages for Eucalyptus globulus plantations reach about 18% in relation to the commercial volume.…”
Section: Dendrometric Characterizationsupporting
confidence: 90%
See 1 more Smart Citation
“…For dendrometric parameters, the average DBH, height and volume are in accordance with what was expected for Eucalyptus urophylla at the age of 8 years, as can be seen in the study of Trugilho et al (2010). Regarding the bark percentage, the results are in harmony with the studies obtained by Ramalho et al (2019) who found values for Eucalyptus urograndis between 10 and 18%. In a general way, according to Neiva et al (2018) bark percentages for Eucalyptus globulus plantations reach about 18% in relation to the commercial volume.…”
Section: Dendrometric Characterizationsupporting
confidence: 90%
“…Despite this, based on Evangelista et al (2010) research, the results are in accordance with the species expectation and there was no influence on the wood classification, whereas in both sites it fits as a light-wood (<0.50 g cm -3 ). Ramalho et al (2019) explain that the basic density of wood can significantly vary depending on age, origin, forestry treatments, spacing and growth rate. As there were no variations in dendrometric and genotypic aspects, the differences observed can be attributed to external factors such as temperature, direction and speed of the winds that causes changes in the tree's cells promoting substantial modification in the density of the wood and production of reaction wood (BRAZ et al, 2014).…”
Section: Physical and Anatomical Characterization Of Woodmentioning
confidence: 99%
“…This high value can be assigned to the lower tree density. Specifically, since chestnut trees are sensitive to the competition with other trees [69,70], the high spacing among the plants could promoted plant growth [71,72] and, therefore, root development. However, we cannot exclude that the low plant density could have also promoted a wider distribution of the root system [73].…”
Section: Discussionmentioning
confidence: 99%
“…Asthon and Kelty [ 15 ] also documented that very high or low density may influence the h growth of species, conditions that were sampled in the current study that may therefore increase the correlation between the SF and the SDI. In addition, the h-dbh ratio (calculated by dividing the h by the dbh) has been described as a measure related to the stand density that increases in closed spaces [ 37 , 38 , 39 ], affecting dominant and codominant trees [ 40 , 41 ]. Therefore, stand density may influence the estimation of the SF.…”
Section: Discussionmentioning
confidence: 99%